Investigation of the Activity of Agomelatine on Some Female Reproductive Hormones in an Experimental Abortion Model - Sayin, Orhan; Bozyil, Ahmed Sait; Pervin, Mehtap; Oz, Zeynep Dila; Ozdede, Mehmet Ridvan; Tan, Fatih; Kacar, Emine (Wiley, 2025)
[Abstract Not Available]
Keywords: Abortion; Agomelatine; Pregnancy; Rat; ELISA